MAKNA SIMBOLIK TRADISI LISAN DALAM ADAT ISTIADAT PERKAWINAN MASYARAKAT MELAYU - Amelia Agustina; Akhyaruddin Akhyaruddin; Ade Bayu Saputra; Andiopenta Purba (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
customs in Tanjung Jabung Timur Regency, Indonesia. This study used a qualitative method with a literature review. The main source of data is the book Adat Istiadat Perkawinan dan Hukum Adat Daerah Kabupaten Tanjung Jabung Timur (Marriage Customs and Local Customary Law in Tanjung Jabung Timur Regency) by Effendi (2018), which contains documentation of traditional marriage Seloko. Data analysis was conducted using Roland Barthes' semiotic theory through the stages of signifier, signified, denotative meaning, and connotative meaning. The validity of the data was strengthened through source and technique triangulation by confirming with local customary institutions. The results of the study show that seloko in the traditional marriage procession contains various symbolic meanings related to responsibility, family honor, deliberation, ethics in household management, wisdom, solidarity, and respect for parents. Each stage of the tradition, from merisik to hari labuh, contains seloko that reinforces cultural messages and strengthens the identity of the Malay community. This study confirms that seloko is not merely an oral tradition but also a representation of local wisdom that is still relevant to the community’s social life.